Strategic Management Based on Perceived Brand Innovativenees Multi-Site Study at SDIT Nurul Anshar and SDN 4 Curah Jeru Situbondo District - Mundiri, Akmal; Agustina, Rifka Sri (Global Education Journal, 2024)
Brand development in improving brand quality at the elementary school (SD) level, namely SDIT Nurul Anshar and SDN 4 Curah Jeru, Situbondo Regency. Brand Innovation is defined to shape public perception, build public trust in the brand, build public love for the brand. The purpose of this article is to explain how as a leader you can develop a school brand to be better, where society currently really needs quality and superior schools to be a place of learning for its children, therefore a brand that is proven to be good will invite the public's trust to become the school of choice. This research uses a qualitative approach by interviewing school principals, teachers, parents, students, and the community as the main respondents. The data collected was then analyzed thematically to identify patterns and findings that emerged regarding the development of the school brand and its impact on the school and community. The research results show that brand development has a positive impact on school quality. Now many schools are following brand innovation methods that can improve school quality. This is achieved by school principals, teachers, students, and the community who can work together to achieve goals. There are several factors that influence school brand development, namely strategic planning which includes positioning, differentiation, and brand service processes. Followed by strategic implementation, namely developing superior programs, developing achievements, and forming character. In addition, this article highlights the importance of support and collaboration between school principals, teachers, students, parents, and the community to achieve optimal results. This research also provides a better understanding of the role of school principals in developing brands. The practical implication of this research is the importance of developing a school brand through appropriate training and education. By developing a school brand, it is hoped that it can improve school quality, community commitment and trust, which will ultimately have a positive impact on education in schools.